Faham tentang Larangan Shalat Jumat Bagi Wanita di Gorontalo - Dulsukmi Kasim (Al-Ulum, 2019)
This article observes the belief of prohibition to do Jumat pray for women moslem on east Bulotalangi village in Bone Bolango regency. There are three mosques in that villages, but only one mosque, namely al-Hidayah mosque, which applied the belief. however, the women came to the mosque on Friday to pray dhuhur. they were leaded by one of man as the priest. the belief has convinced since 1994, which taught by Karim Daud. He was a priest in that mosque. there was no accurate source why they did the belief. the belief is still applied until today, because of four factors, namely 1) the lack of religious knowledge of the followers; 2) the lack of government and Islamic pioneer attention to the condition; 3) The fanaticism of the followers to do the belief; 4) No attention from the priests toward the problem.